IMPLEMENTASI SISTEM E-VOTING BERBASIS ANDROID PADA SISTEM PEMILIHAN LANGSUNG DI LINGKUNGAN UNIVERSITAS ADVENT INDONESIA MENGGUNAKAN FRAMEWORK LARAVEL - Yulianus Palopak (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
The objective to be achieved in this study is to provide a system that can be used by voters in choosing the desired candidate through Android-based smartphone media. The implementation of the e-voting system in the selection of outstanding students at Universitas Advent Indonesia (UNAI) showed that the interest in using the e-voting system was very high and it was very helpful in the selection process. More than 84% of voters who used the e-voting system in the selection of UNAI's outstanding students gave an excellent response and rating on the use of the application. From all of the users, 81 voters gave a brief review of the application and it usage, 68.4% of them gave a brief review that the application was very helpful in the selection process of outstanding students at UNAI, while 6.3% stated that the application still needed improvement. In the future this system needs to be equipped with an analysis of the system response when using it simultaneously by many users.